Cold thermal energy storage for cryogenic applications in enhancing the battery life of a UAV - Somu, Arvind Kanmaya (Nanyang Technological University, 2020)
Unmanned Aerial Vehicles (UAV) have been commercialized for many different purposes, satisfying other objectives. However, the battery performance of a typical Lithium-ion battery does not give the full potential of the UAV due to the short time frame. This report aims to investigate and create a prototype which comprises of Phase Change Material (PCM) to solve the problem of overheating Lithium-ion battery. Previous researches have shown to prove the theory that PCM reduces the temperature on a lithium- ion battery. But these studies were performed on other forms of electronics such as a battery-operated scooter. Current solutions aim at re-creating a new technology, instead of focusing on existing batteries. What made this project unique was that it could be practical for all current existing UAVs, instead of just using it for a new design. PCM used in this project was water to make things simple. Based on simulations conducted by the author, the use of PCM enabled UAV battery temperature to decrease by a maximum of 81.7K. The time taken for the lithium-ion battery to reach its Risk of Thermal Runway Temperature (RTRT) increased by about 28.6 minutes. The time taken for the lithium-ion battery to reach its Critical Thermal Runway Temperature (CTRT) increased by about 41.7 minutes.